Managerial Perceptions on Internal Business Process Perspective in Commercial Banks of Nepal - Parajuli, Dilip (The Batuk, 2021)
This paper aims to explore managerial perceptions on the internal business process perspective in Nepalese commercial banks. A set of questionnaire consisting five-point Likert-type scale statements was administered to collect data from sample units; state-owned banks, private banks, and joint venture banks. The findings indicate that customer need satisfaction has been perceived as the top priority measure of the internal business process perspective in Nepalese banks. Distribution reach and process delivery aspects of the internal process perspective have also got more preferences as per the perceptions of the managers. However, some other aspects such as service cycle duration, a sufficient number of training hours, and a comprehensive innovation process seem to be less preferred. The overall results show that the internal business process as per the response is satisfactory.